Pharmacological modulation of chloride channels as a therapeutic strategy for neurological disorders - Wang, Zhiyu; Choi, Kaylee (Frontiers in Physiology, 2023)
Chloride homeostasis is critical in the physiological functions of the central nervous system (CNS). Its concentration is precisely regulated by multiple ion-transporting proteins such as chloride channels and transporters that are widely distributed in the brain cells, including neurons and glia. Unlike ion transporters, chloride channels provide rapid responses to efficiently regulate ion flux. Some of chloride channels are also permeable to selected organic anions such as glutamate and γ-aminobutyric acid, suggesting neuroexcitatory and neuroinhibitory functions while gating. Dysregulated chloride channels are implicated in neurological disorders, e.g., ischemia and neuroinflammation. Modulation of chloride homeostasis through chloride channels has been suggested as a potential therapeutic approach for neurological disorders. The drug design for CNS diseases is challenging because it requires the therapeutics to traverse the blood-brain-barrier. Small molecules are a well-established modality with better cell permeability due to their lower molecular weight and flexibility for structure optimization compared to biologics. In this article, we describe the important roles of chloride homeostasis in each type of brain cells and introduce selected chloride channels identified in the CNS. We then discuss the contribution of their dysregulations towards the pathogenesis of neurological disorders, emphasizing the potential of targeting chloride channels as a therapeutic strategy for CNS disease treatment. Along with this literature survey, we summarize the small molecules that modulate chloride channels and propose the potential strategy of optimizing existing drugs to brain-penetrants to support future CNS drug discovery.